ABC protein CgABCF2 is required for asexual and sexual development, appressorial formation and plant infection in Colletotrichum gloeosporioides. (September 2017) - Zhou, Zongshan; Wu, Jianyuan; Wang, Meiyu; Zhang, Junxiang
Abstract: ATP-binding cassette (ABC) proteins are exclusively found in both prokaryotes and eukaryotes. In this study, we have characterized a gene from Glomerella leaf spot pathogen Colletotrichum gloeosporioides that encodes an ABC protein, whose function to date remains unknown. We designated this gene as CgABCF2 . Deletion of CgABCF2 showed drastic reduction both growing rate and conidial production in C . gloeosporioides . The Δcgabcf2 mutant did not form the appressoria, lost the capability to infect apple and failed to form lesions on the wounded leaves and fruits. The C . gloeosporioides native CgABCF2 fully recovered defect of the Δcgabcf2 mutant. These data indicated that CgABCF2 was required for fungal development and invasion. The transcriptions of six pectolytic enzymes genes ( CgPG1, CgPG2, pnl-1, pnl-2, pel A and pel B) significantly reduced in the Δcgabcf2 mutant, indicating that deletion of CgABCF2 impaired the fungal necrotrophic growth. In addition, CgABCF2 mediated sexual development through the positive regulation of the gene MAT1-2-1 expression. These results indicated that CgABCF2 underlies the complex process governing morphogenesis, sexual and asexual reproduction, appressorial formation and pathogenicity in C . gloeosporioides . Highlights: CgABCF2 was first identified and characterized in the Colletotrichum gloeosporioides. CgABCF2 deletion mutant drastically reduced hyphal growth and conidial production. CgABCF2 deletion mutant impaired the transcriptions of the pectolytic enzymes genes. CgABCF2 was indispensable for the appressorial formation and pathogenicity.